Cobalt-based composite catalyst and preparation method and application thereof

By preparing cobalt-based composite catalysts, the mixing of magnesium hydroxide nanosheets and cobalt salt precursors and the ion exchange process of cerium salt precursors is solved, and the existing precious metal catalysts are solved in the high cost and poor stability of propane exhaust gas treatment is achieved. Highly efficient and low-cost propane removal effect.

CN119455959AActive Publication Date: 2025-02-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310978104.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-18
Estimated Expiration
2043-08-04

AI Technical Summary

Technical Problem

The existing precious metal catalysts have problems such as large amounts, high cost, low dispersion and poor stability in propane exhaust gas treatment, and the complex preparation process is not conducive to large-scale industrial production.

Method used

Using a cobalt-based composite catalyst, the cobalt-based composite catalyst is mixed with the cobalt salt precursor in the presence of water to form cobalt-hydroxide nanosheets, and then ion-exchanged with the cerium salt precursor. After calcination, the cobalt-based composite catalyst is obtained. .

Benefits of technology

It has achieved a high propane removal rate and high conversion rate and is suitable for low-concentration propane removal system. It has low cost, simple process and good stability, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455959A_ABST
    Figure CN119455959A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, and discloses a cobalt-based composite catalyst and a preparation method and application thereof.The cobalt-based composite catalyst contains 25-50 wt% of cobalt element, 5-10 wt% of cerium element and 0.5-2 wt% of magnesium element according to elements; the oxygen vacancy content of the cobalt-based composite catalyst is 20-60%, and the specific surface area of the cobalt-based composite catalyst is 20-200m < 2 > / g. The cobalt-based composite catalyst provided by the invention is low in cost, high in propane removal rate, high in conversion rate and suitable for a low-concentration propane removal system, and the method provided by the invention can enable the active metal precursor and the carrier to be fully fused and mutually changed, so that more doped oxygen vacancies are constructed to adsorb and activate propane, and the overall catalytic performance of the catalyst is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation, and in particular to a cobalt-based composite catalyst and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) participate in atmospheric photochemical reactions and can form secondary organic aerosols, which may be one of the main sources of haze and are the focus of environmental protection at home and abroad. In the process of directional oxidation in coal chemical production, incomplete reactions often occur, resulting in the enrichment of VOCs gas in the exhaust gas or circulating carrier gas of the device, which not only leads to the risk of explosion in the chemical production process, but also forms photochemical phenomena, causing pollution to the surrounding environment.

[0003] Catalytic oxidation is a common technology for VOCs treatment. Propane, as a typical VOCs tail gas, is widely present in the fields of liquefied natural gas, compressed natural gas and liquefied petroleum gas. One of the effective treatment methods is catalytic oxidation. Currently, supported precious metal catalysts are widely used. However, precious metals themselves are expensive and the mining and purification technology is cumbersome, which makes the problems of large amount of precious metal catalysts, high cost, low dispersion and poor stability still exist. The development of efficient and stable non-precious metal catalysts is crucial to the development of this technology, especially in terms of cost control.

[0004] CN107876060A discloses a cerium cobalt catalyst for complete oxidation of propane and its preparation method and application, wherein cobalt salt and cerium salt are added to a tert-butyl alcohol solution containing an inorganic acid, a polyether surfactant and sodium dodecyl sulfate and stirred until completely dissolved, then placed under 20-70°C for reaction for 1-3 hours, then freeze-dried and roasted to obtain a cerium cobalt catalyst for complete oxidation of propane. The catalyst prepared by the prior art has the advantages of high activity, low cost and high stability, but it requires additional addition of surfactants, and requires extreme conditions such as liquid nitrogen and refrigerator freezing, strict condition control and high energy consumption.

[0005] CN113856690A discloses a cobalt-based catalyst for catalytic combustion of low-concentration methane, its preparation method and application. The Ni-Co-based spinel doped with rare earth element Ce is prepared by microwave single mode combined with self-propagating combustion method. The methane conversion rate can reach more than 90% under 440°C conditions, and it shows high catalytic stability under 5vol% H2O and 5vol% CO2 conditions. The catalyst has the characteristics of low cost, simple preparation process, large specific surface area, good activity stability, etc. However, the equipment required for the preparation of the prior art is complicated, which is not conducive to industrial large-scale production. Summary of the invention

[0006] The purpose of the present invention is to provide a non-precious metal cobalt-based composite catalyst which has high propane removal rate and high conversion rate and is suitable for a low-concentration propane removal system.

[0007] In order to achieve the above object, the first aspect of the present invention provides a cobalt-based composite catalyst, which contains 25-50wt% of cobalt, 5-10wt% of cerium, and 0.5-2wt% of magnesium in terms of elements; the cobalt-based composite catalyst has an oxygen vacancy content of 20-60% and a specific surface area of ​​20-200m 2 / g.

[0008] The second aspect of the present invention provides a method for preparing the cobalt-based composite catalyst described in the first aspect, comprising the following steps:

[0009] (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-20 nm, and the specific surface area is 100-500 m 2 / g;

[0010] (2) drying the mixture I to obtain the cobalt hydroxide nanosheets; the drying temperature is not higher than 40° C.;

[0011] (3) crystallizing the cobalt hydroxide nanosheets and the cerium salt precursor in the presence of water to obtain a mixture II; the molar ratio of the cobalt element in the cobalt hydroxide nanosheets to the cerium element in the cerium salt precursor is 1:0.01-1 in terms of metal elements;

[0012] (4) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based composite catalyst; the conditions of the second calcination treatment include: a temperature of 200-800° C., a heating rate of 2-20° C. / min, and a time of 2-4 h.

[0013] The third aspect of the present invention provides a cobalt-based composite catalyst prepared by the method described in the second aspect.

[0014] The fourth aspect of the present invention provides use of the cobalt-based composite catalyst described in the first aspect or the third aspect in the treatment of propane-containing gas.

[0015] The present invention provides a non-precious metal catalyst with a simple and controllable preparation process for the propane tail gas efficient removal technology in the petrochemical production process. The precursor ultra-thin magnesium hydroxide is used as a template by an ion exchange method. Cobalt hydroxide nanosheets are formed in situ by the difference in solubility product. Then, in the presence of water, the cobalt hydroxide nanosheets are further ion exchanged with the cerium salt precursor to obtain a cobalt-cerium mixed hydroxide precursor, which is finally obtained by calcination. The catalyst surface defect sites are efficiently constructed and the particle size of the catalyst particles is controlled by regulating the cobalt-cerium mixing ratio, the salt solution concentration and the calcination temperature, thereby promoting the adsorption and activation of the substrate and improving the overall catalytic performance.

[0016] In the cobalt-based composite catalyst provided by the present invention, new catalytic sites are constructed at the interface between the active substance Co3O4 and the carrier CeO2. The method provided by the present invention can make the active metal precursor and the carrier fully merge and change each other, construct more doped oxygen vacancies to adsorb and activate propane, and enhance the overall catalytic performance of the catalyst.

[0017] The cobalt-based composite catalyst provided by the present invention is a non-precious metal catalyst, which has low cost and is highly efficient and stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is a transmission electron microscope image of magnesium hydroxide nanosheets in Example 1;

[0019] Figure 2 is a transmission electron microscope image of magnesium hydroxide nanosheets in Example 1;

[0020] Figure 3 is a transmission electron microscope image of cobalt hydroxide nanosheets in Example 1;

[0021] Figure 4 is a transmission electron microscope image of the cobalt-based composite catalyst of Example 1;

[0022] Figure 5 is the X-ray diffraction (XRD) pattern of the cobalt-based composite catalyst of Example 1;

[0023] Figure 6 is an element distribution diagram of the cobalt-based composite catalyst of Example 1;

[0024] Figure 7 is the distribution diagram of Co element in the cobalt-based composite catalyst of Example 1;

[0025] Figure 8 is a distribution diagram of Ce element in the cobalt-based composite catalyst of Example 1;

[0026] Fig. 9 This is the distribution diagram of the O element in the cobalt-based composite catalyst of Example 1. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] As mentioned above, the first aspect of the present invention provides a cobalt-based composite catalyst, which contains 25-50wt% of cobalt, 5-10wt% of cerium, and 0.5-2wt% of magnesium in terms of elements; the cobalt-based composite catalyst has an oxygen vacancy content of 20-60% and a specific surface area of ​​20-200m 2 / g.

[0029] Preferably, calculated on the basis of elements, the cobalt-based composite catalyst contains 40-50 wt% of cobalt, 7-10 wt% of cerium, and 0.5-2 wt% of magnesium.

[0030] Preferably, the cobalt-based composite catalyst has an oxygen vacancy content of 30-40% and a specific surface area of ​​50-100 m 2 / g.

[0031] In the present invention, the cobalt element, cerium element and magnesium element are all present in the cobalt-based composite catalyst in the form of oxides.

[0032] Preferably, the average particle diameter of the cobalt-based composite catalyst is 1-20 nm, more preferably 1-10 nm.

[0033] The cobalt-based composite catalyst provided by the present invention has a high catalytic effect on raw gas with a propane concentration of ≤5v%, a reaction mass space velocity of 60000mL / g / h, a propane conversion rate of ≥1% above 100°C, a propane conversion rate of ≥99% above 350°C, stability of ≥300h, and can make the residual propane volume concentration in the raw gas ≤50ppm after the reaction.

[0034] As mentioned above, the second aspect of the present invention provides a method for preparing the cobalt-based composite catalyst described in the first aspect, comprising the following steps:

[0035] (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-20 nm, and the specific surface area is 100-500 m2 / g;

[0036] (2) drying the mixture I to obtain the cobalt hydroxide nanosheets; the drying temperature is not higher than 40° C.;

[0037] (3) crystallizing the cobalt hydroxide nanosheets and the cerium salt precursor in the presence of water to obtain a mixture II; the molar ratio of the cobalt element in the cobalt hydroxide nanosheets to the cerium element in the cerium salt precursor is 1:0.01-1 in terms of metal elements;

[0038] (4) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based composite catalyst; the conditions of the second calcination treatment include: a temperature of 200-800° C., a heating rate of 2-20° C. / min, and a time of 2-4 h.

[0039] pass Figure 1 and Figure 2 It can be seen from the transmission electron microscope image of the magnesium hydroxide nanosheet shown that the magnesium hydroxide nanosheet of the present invention is in an irregular sheet shape. The inventors of the present invention have found in their research that the cobalt-based composite catalyst prepared by using the magnesium hydroxide nanosheet of this size as a template in combination with the other technical features of the present invention has a more excellent catalytic performance.

[0040] Preferably, in step (1), the average thickness of the magnesium hydroxide nanosheets is 1-10 nm.

[0041] According to a preferred specific embodiment, the method further comprises: first mixing the magnesium oxide particles with water to obtain the magnesium hydroxide nanosheets; the conditions of the first mixing include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 10 min to 24 h.

[0042] Preferably, the amount of the magnesium oxide particles used is such that the initial concentration of magnesium in the reaction system formed by the first mixing is 1.0-1.5 mol / L.

[0043] Preferably, the magnesium oxide particles are obtained by subjecting a magnesium precursor to a first calcination treatment; and the average particle diameter of the magnesium oxide particles is 5-30 nm.

[0044] Preferably, the conditions of the first calcination treatment include: temperature of 600-1000° C., heating rate of 2-20° C. / min, time of 2-4 h, and air flow rate of 10-100 mL / min.

[0045] Preferably, the magnesium precursor is selected from at least one of light magnesium oxide, basic magnesium carbonate, and magnesium chloride hexahydrate.

[0046] According to a preferred specific embodiment, the magnesium precursor is basic magnesium carbonate and / or magnesium chloride hexahydrate, and the second mixing time in step (1) is 2-5 hours. The inventors of the present invention have found in research that using basic magnesium carbonate and / or magnesium chloride hexahydrate as a magnesium precursor can significantly shorten the reaction time of the second mixing and improve the production efficiency of the cobalt-based composite catalyst.

[0047] According to another preferred embodiment, the magnesium precursor is light magnesium oxide, and the second mixing time in step (1) is 20-30 hours. The inventors of the present invention have found in their research that the cobalt-based composite catalyst prepared by using light magnesium oxide as a magnesium precursor has better catalytic performance.

[0048] In the present invention, after the solid-liquid mixture containing magnesium hydroxide nanosheets is obtained by the first mixing, the cobalt salt precursor can be directly introduced therein to perform the second mixing, or the solid-liquid mixture containing magnesium hydroxide nanosheets can be sequentially subjected to water washing, suction filtration, and drying steps to obtain the magnesium hydroxide nanosheets, and then the magnesium hydroxide nanosheets are used to participate in the second mixing. The present invention will not be described in detail here, and those skilled in the art should not be construed as limiting the present invention.

[0049] The magnesium hydroxide nanosheets obtained by the present invention may also contain the magnesium oxide particles that have not reacted completely. When participating in the second mixing in step (1), the magnesium hydroxide nanosheets that have not reacted completely can continue to react to obtain magnesium hydroxide nanosheets. At the same time, the magnesium hydroxide nanosheets are used as templates and the cobalt hydroxide nanosheets are formed in situ by an ion exchange method using the difference in solubility product.

[0050] pass Figure 3 It can be seen from the transmission electron microscope image of the cobalt hydroxide nanosheet shown in that the cobalt hydroxide nanosheet of the present invention is in an irregular sheet shape and the thickness of the nanosheet is very thin.

[0051] Preferably, in step (1), the amount of the cobalt salt precursor is such that the initial concentration of the cobalt element in the reaction system formed by the second mixing is 0.1-2 mol / L, more preferably 0.4-0.8 mol / L. The inventors have found that under this more preferred condition, the propane removal rate and catalyst conversion rate of the cobalt-based composite catalyst obtained by the present invention are higher.

[0052] Preferably, in step (1), the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1-2, calculated as metal elements.

[0053] Preferably, in step (1), the cobalt salt precursor is selected from at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate heptahydrate, and cobalt acetate tetrahydrate.

[0054] More preferably, in step (1), the cobalt salt precursor is cobalt nitrate hexahydrate. The inventors of the present invention have found in their research that, compared with other water-soluble cobalt salts, the cobalt-based composite catalyst prepared by selecting cobalt nitrate hexahydrate as the cobalt salt precursor has better catalytic activity and higher propane conversion rate.

[0055] Preferably, in step (1), the second mixing conditions include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 2-30 h.

[0056] Preferably, in step (2), the drying temperature is 20-40°C, preferably 20-30°C, and the time is 20-26h. The inventors of the present invention have found that when the drying conditions are controlled within the preferred range, the ion exchange effect between the cobalt hydroxide nanosheets and the cerium salt precursor is better, thereby preparing a cobalt-based composite catalyst with higher catalytic activity.

[0057] In step (2) of the present invention, before the drying treatment, a pre-treatment method of washing and filtering is also included, which will not be described in detail herein and should not be construed as a limitation to the present invention by those skilled in the art.

[0058] Preferably, in step (3), the molar ratio of the cobalt element in the cobalt hydroxide nanosheets to the cerium element in the cerium salt precursor is 1:0.025-1, calculated as metal element.

[0059] Preferably, in step (3), the amount of the cerium salt precursor used is such that the initial concentration of cerium element in the reaction system formed by the crystallization treatment is 0.01-2.5 mol / L.

[0060] Preferably, in step (3), the cerium salt precursor is selected from at least one of cerous nitrate hexahydrate, cerous chloride heptahydrate, and cerous sulfate tetrahydrate.

[0061] Preferably, in step (3), the conditions of the crystallization treatment include: temperature of 100-120° C. and time of 4-12 h.

[0062] The present invention has no particular limitation on the equipment for performing the crystallization treatment, as long as the conditions required by the present invention can be met. For example, the crystallization treatment is performed in an oven. The present invention will not be elaborated herein, and those skilled in the art should not understand it as a limitation of the present invention.

[0063] In the crystallization process of the present invention, the cobalt hydroxide nanosheets and the cerium salt precursor are further ion exchanged to obtain the mixture II containing the cobalt-cerium mixed hydroxide precursor. At the same time, the water in the crystallization reaction system gradually evaporates to finally obtain the dry mixture II.

[0064] Preferably, in step (4), the conditions of the second calcination treatment include: a temperature of 200-400°C, a heating rate of 3-15°C / min, a time of 2-3h, and an air flow rate of 10-100mL / min. The inventors of the present invention have found in their research that under the preferred second calcination treatment conditions, the propane removal rate and catalyst conversion rate of the cobalt-based composite catalyst provided by the present invention are higher, and the catalytic performance is more excellent.

[0065] As mentioned above, the third aspect of the present invention provides a cobalt-based composite catalyst prepared by the method described in the second aspect.

[0066] from Figure 4 It can be seen from the transmission electron microscope image of the cobalt-based composite catalyst that the cobalt-based composite catalyst particles provided by the present invention have a small particle size and a uniform size and have a higher specific surface area.

[0067] Figure 5 is the XRD spectrum of the cobalt-based composite catalyst, wherein 2-theta is the angle of 2θ at which the x-ray diffractometer scans the entire diffraction area, which exists as the angle change and the horizontal coordinate of the x-ray diffraction spectrum; Co3O4@CeO2 indicates that the cobalt-based composite catalyst is a CeO2-supported catalyst. Figure 5 It can be seen that Co3O4 and CeO2 show obvious diffraction peaks respectively.

[0068] Since the magnesium content in the cobalt-based composite catalyst of the present invention does not reach the detection limit of XRD, the present invention uses inductively coupled plasma technology (ICP) to detect the magnesium content in the cobalt-based composite catalyst.

[0069] Figure 6 Co3O4@CeO2 indicates that the cobalt-based composite catalyst is a CeO2-supported catalyst. Figures 6 to 9 It can be seen from the element distribution diagram that the Co, Ce and O elements are evenly distributed, so that CeO2 can penetrate into Co3O4 well and enhance the synergistic interaction of Co-O-Ce.

[0070] In the cobalt-based composite catalyst provided by the present invention, there are Co-Ov-Ce defects (oxygen vacancies) on the surface between the cobalt element, the cerium element and the oxygen element. Such doped oxygen vacancies can construct new catalytic sites, thereby achieving the beneficial effects of enhancing the catalyst adsorption and activation of propane.

[0071] The "Ov" mentioned in the present invention refers to the oxygen vacancies on the catalyst surface.

[0072] As mentioned above, the fourth aspect of the present invention provides the use of the cobalt-based composite catalyst described in the first aspect or the third aspect in the treatment of propane-containing gas.

[0073] Preferably, the concentration of propane in the propane-containing gas is ≤5v%.

[0074] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0075] In the following examples, the specific surface areas of magnesium hydroxide nanosheets and cobalt-based composite catalysts were determined by nitrogen adsorption-desorption method.

[0076] In the following examples, an XPS ray photoelectron spectrometer (manufacturer: Thermo Fisher Scientific, model: Thermo Kalpha) was used to test the oxygen vacancy content of the cobalt-based composite catalyst.

[0077] Example 1

[0078] S1: The magnesium precursor was first calcined at 750°C for 2 h at an air flow rate of 30 mL / min and a heating rate of 5°C / min to obtain magnesium oxide particles (with an average particle diameter of 20 nm). The magnesium oxide particles were first mixed with water at 75 rpm and 25°C for 24 h, and then washed, filtered, and dried to obtain magnesium hydroxide nanosheets (with an average thickness of 3 nm and a specific surface area of ​​250 m 2 / g);

[0079] The magnesium precursor is basic magnesium carbonate; the amount of magnesium oxide particles used is 0.0125 mol, and the amount of magnesium oxide particles used is such that in the first mixed system, the initial concentration of magnesium element is 1.25 mol / L;

[0080] S2: In the presence of water, all the magnesium hydroxide nanosheets obtained in step S1 are mixed with the cobalt salt precursor at 100 rpm and 25° C. for a second time for 3 hours to obtain a mixture I containing cobalt hydroxide nanosheets;

[0081] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);

[0082] S3: washing the mixture I with water, filtering it, and then drying it at 25° C. for 24 h to obtain cobalt hydroxide nanosheets;

[0083] S4: in the presence of water, the cobalt hydroxide nanosheets and the cerium salt precursor are mixed evenly and then placed in an oven at 120° C. for crystallization treatment for 12 hours to obtain a mixture II;

[0084] The cerium salt precursor is cerium nitrate hexahydrate, and the amount used is 0.0005 mol; the amount of the cerium salt precursor is such that in the reaction system formed by the crystallization treatment, the initial concentration of cerium element is 0.0125 mol / L, and the molar ratio of the cobalt element in the cobalt hydroxide nanosheet to the cerium element in the cerium salt precursor is 1:0.025 in terms of metal element;

[0085] S5: subjecting the mixture II to a second calcination treatment at an air flow rate of 50 mL / min, a heating rate of 3° C. / min, and 300° C. for 2 h to obtain a cobalt-based composite catalyst.

[0086] Example 2

[0087] S1: The magnesium precursor was first calcined at 750°C for 2 h at an air flow rate of 40 mL / min and a heating rate of 3°C / min to obtain magnesium oxide particles (with an average particle diameter of 25 nm). The magnesium oxide particles were first mixed with water at 120 rpm and 25°C for 24 h, and then washed, filtered, and dried to obtain magnesium hydroxide nanosheets (with an average thickness of 2 nm and a specific surface area of ​​170 m 2 / g);

[0088] The magnesium precursor is light magnesium oxide; the amount of magnesium oxide particles used is 0.0125 mol, and the amount of magnesium oxide particles used is such that the initial concentration of magnesium in the first mixed system is 1.25 mol / L;

[0089] S2: In the presence of water, all the magnesium hydroxide nanosheets obtained in step S1 are mixed with the cobalt salt precursor at 80 rpm and 25° C. for a second time for 24 hours to obtain a mixture I containing cobalt hydroxide nanosheets;

[0090] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);

[0091] S3: washing the mixture I with water, filtering it, and then drying it at 25° C. for 24 h to obtain cobalt hydroxide nanosheets;

[0092] S4: in the presence of water, the cobalt hydroxide nanosheets and the cerium salt precursor are mixed evenly and then placed in an oven at 100° C. for crystallization treatment for 4 hours to obtain a mixture II;

[0093] The cerium salt precursor is cerium chloride heptahydrate, and the amount used is 0.0005 mol; the amount of the cerium salt precursor is such that in the reaction system formed by the crystallization treatment, the initial concentration of cerium element is 0.0125 mol / L, and the molar ratio of the cobalt element in the cobalt hydroxide nanosheet to the cerium element in the cerium salt precursor is 1:0.025 in terms of metal element;

[0094] S5: subjecting the mixture II to a second calcination treatment at an air flow rate of 30 mL / min, a heating rate of 7° C. / min, and 400° C. for 3 h to obtain a cobalt-based composite catalyst.

[0095] Example 3

[0096] This embodiment is carried out using a process similar to that of Embodiment 1, except that in step S2, the cobalt salt precursor is cobalt chloride hexahydrate; the amount of the cobalt salt precursor used is such that the initial concentration of the cobalt element in the reaction system formed by the second mixture is 0.2 mol / L, and the type and amount of the cobalt salt precursor remain unchanged;

[0097] A cobalt-based composite catalyst is prepared.

[0098] Example 4

[0099] This embodiment adopts a process similar to that of Embodiment 1, except that in step S4, the molar ratio of the cobalt element in the cobalt hydroxide nanosheets to the cerium element in the cerium salt precursor is 1:0.015, calculated as the metal element; the type and amount of the cerium salt precursor remain unchanged;

[0100] A cobalt-based composite catalyst is prepared.

[0101] Example 5

[0102] This embodiment adopts a process similar to that of Embodiment 1, except that in step S5, the temperature of the second calcination treatment is adjusted from 300° C. to 500° C., and the other conditions remain unchanged;

[0103] A cobalt-based composite catalyst is prepared.

[0104] Example 6

[0105] This embodiment adopts a process similar to that of Embodiment 2, except that this embodiment does not perform the first roasting treatment, and directly uses light magnesium oxide to participate in the first mixing, specifically:

[0106] S1: Light magnesium oxide and water were first mixed at 75 rpm and 25°C for 24 h, and then washed, filtered, dried, and other steps to obtain magnesium hydroxide nanosheets (average thickness of 2 nm and specific surface area of ​​180 m 2 / g);

[0107] The dosage of light magnesium oxide is 0.0125 mol, and the initial concentration of light magnesium oxide in the first mixed system is 1.25 mol / L;

[0108] S2: In the presence of water, all the magnesium hydroxide nanosheets obtained in step S1 are mixed with the cobalt salt precursor at 90 rpm and 25° C. for a second time for 24 hours to obtain a mixture I containing cobalt hydroxide nanosheets;

[0109] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);

[0110] S3: washing the mixture I with water, filtering it, and then drying it at 25° C. for 24 h to obtain cobalt hydroxide nanosheets;

[0111] S4: in the presence of water, the cobalt hydroxide nanosheets and the cerium salt precursor are mixed evenly and then placed in an oven at 100° C. for crystallization treatment for 4 hours to obtain a mixture II;

[0112] The cerium salt precursor is cerium chloride heptahydrate, and the amount used is 0.0005 mol; the amount of the cerium salt precursor is such that in the reaction system formed by the crystallization treatment, the initial concentration of cerium element is 0.0125 mol / L, and the molar ratio of the cobalt element in the cobalt hydroxide nanosheet to the cerium element in the cerium salt precursor is 1:0.025 in terms of metal element;

[0113] S5: subjecting the mixture II to a second calcination treatment at an air flow rate of 30 mL / min, a heating rate of 7° C. / min, and 400° C. for 3 h to obtain a cobalt-based composite catalyst.

[0114] Example 7

[0115] This embodiment adopts a process similar to that of Embodiment 1, except that in step S3, the drying temperature is adjusted from 25°C to 40°C, and the other conditions remain unchanged;

[0116] A cobalt-based composite catalyst is prepared.

[0117] Example 8

[0118] This embodiment is carried out using a process similar to that of Embodiment 1, except that in step S2, the cobalt salt precursor cobalt nitrate hexahydrate is replaced with an equimolar amount of cobalt sulfate heptahydrate, and the rest remain unchanged;

[0119] A cobalt-based composite catalyst is prepared.

[0120] Example 9

[0121] This embodiment adopts a process similar to that of Embodiment 1, except that in step S2, the cobalt salt precursor cobalt nitrate hexahydrate is replaced with cobalt acetate tetrahydrate; specifically:

[0122] Step S2: In the presence of water, all the magnesium hydroxide nanosheets obtained in step S1 are mixed with the cobalt salt precursor at 100 rpm and 25° C. for a second time for 3 hours to obtain a mixture I containing cobalt hydroxide nanosheets;

[0123] The cobalt salt precursor is cobalt acetate tetrahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the second mixed reaction system, the initial concentration of cobalt element is 0.1 mol / L (in terms of metal element, the molar ratio of cobalt element in the cobalt salt precursor to magnesium element in the magnesium hydroxide nanosheets is 1:1).

[0124] The rest remained unchanged to prepare a cobalt-based composite catalyst.

[0125] Comparative Example 1

[0126] This comparative example is carried out using a process similar to that of Example 1, except that in step S2, the amount of cobalt nitrate hexahydrate used as the cobalt salt precursor is 0.00357 mol (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:3.5), and the rest remain unchanged;

[0127] A cobalt-based composite catalyst is prepared.

[0128] Comparative Example 2

[0129] Preparation of Cobalt-based Composite Catalyst by Impregnation Method

[0130] 5.82 g of cobalt nitrate hexahydrate was added to 5 mL of deionized water solution, and then 0.09 g of CeO2 was added to the mixture. The slurry was stirred and evaporated at 110°C until completely dry. It was then calcined at 300°C to obtain a cobalt-based composite catalyst.

[0131] Comparative Example 3

[0132] This comparative example is carried out using a process similar to that of Example 1, except that in step S3, the drying temperature is adjusted from 25°C to 60°C, and the other conditions remain unchanged;

[0133] A cobalt-based composite catalyst is prepared.

[0134] Comparative Example 4

[0135] This comparative example is carried out using a process similar to that of Example 1, except that in step S5, the temperature of the second calcination treatment is adjusted from 300° C. to 900° C., and the other conditions remain unchanged;

[0136] A cobalt-based composite catalyst is prepared.

[0137] The composition and parameter characteristics of the cobalt-based composite catalysts prepared in each example are shown in Table 1.

[0138] Table 1

[0139]

[0140] Test Example 1

[0141] The catalytic propane reaction was tested on a fixed bed. The specific test process is as follows:

[0142] 0.70g of the cobalt-based composite catalyst of the present invention is taken to carry out propane catalytic oxidation reaction, which is carried out on a micro-fixed bed evaluation device gas chromatography online analysis integrated system device. The catalyst tablet is sieved, and catalyst particles (0.4-0.85mm) are selected and loaded into a stainless steel reaction tube with a quartz liner, switched to the required reaction temperature, and propane and air mixed raw gas are respectively introduced to react, wherein the propane volume concentration in the raw gas is 2500ppm, and the air velocity is 60000mL / g / h, and the reaction temperature is controlled by heating. During the reaction process, after each temperature point is stable for 30min, chromatographic sampling is performed for online analysis.

[0143] The cobalt-based composite catalyst provided by the present invention has a high catalytic effect on propane in the raw gas, the reaction mass space velocity is 60000 mL / g / h, the propane conversion rate is ≥1% above 100°C, and the propane conversion rate is ≥99% above 350°C. The present invention exemplarily provides data shown in Table 2 to illustrate the catalytic effect of the cobalt-based composite catalyst prepared in Example 1.

[0144] Propane conversion rate (%) = (volume flow rate of propane in raw gas - volume flow rate of propane in tail gas after reaction) / volume flow rate of propane in raw gas × 100%

[0145] Table 2

[0146] Temperature(℃) Propane conversion rate (%) 100 1.17 125 1.30 150 3.46 175 6.84 200 20.65 225 61.30 250 83.22 275 92.62 300 96.56 325 98.38 350 99.33

[0147] It can be seen from the data in Table 2 that the propane conversion rate is 1.17% at 100°C, and 99.33% at temperatures above 350°C, and the propane conversion is more complete as the temperature increases.

[0148] Test Example 2

[0149] The cobalt-based composite catalysts prepared in the embodiments and comparative examples were used to carry out propane catalytic oxidation reaction. The specific test process is as follows:

[0150] Take 0.35g of the cobalt-based composite catalyst prepared in each example to carry out propane catalytic oxidation reaction, and carry out it on a micro-fixed bed evaluation device gas chromatography online analysis integrated system device. The catalyst tablet is sieved, and the catalyst particles (0.4-0.85mm) are selected and loaded into a stainless steel reaction tube with a quartz liner, switched to the required reaction temperature, and propane and air mixed raw gas are respectively introduced for reaction, wherein the propane volume concentration in the raw gas is 2500ppm, the air velocity is 60000mL / g / h, and the reaction temperature is controlled by heating. During the reaction process, after each temperature point is stable for 30min, the chromatographic sampling is carried out for online analysis.

[0151] Propane conversion rate (%) = (volume flow rate of propane in raw gas - volume flow rate of propane in tail gas after reaction) / volume flow rate of propane in raw gas × 100%

[0152] The cobalt-based composite catalysts prepared in the examples and comparative examples were used to carry out propane catalytic oxidation reaction, and the T 50 and T 90 Value, T 50 , T 90 They represent the reaction temperatures at which propane conversion is 50% and 90%, respectively.

[0153] The results are shown in Table 3.

[0154] Table 3

[0155] <![CDATA[T 50 (℃)]]> <![CDATA[T 90 (℃)]]> Example 1 217 268 Example 2 212 263 Example 3 220 273 Example 4 230 336 Example 5 225 300 Example 6 230 310 Example 7 251 335 Example 8 250 338 Example 9 253 292 Comparative Example 1 265 370 Comparative Example 2 235 348 Comparative Example 3 290 380 Comparative Example 4 269 365

[0156] It can be seen from the data in Table 3 that when the cobalt-based composite catalyst obtained by the technical solution provided by the present invention is used for catalytic oxidation of propane, T 50 and T 90 The lower the value, the higher the activity of the catalyst and the better the catalytic performance.

[0157] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cobalt-based composite catalyst, characterized in that: Calculated by elements, the cobalt-based composite catalyst contains 25-50wt% of cobalt, 5-10wt% of cerium, and 0.5-2wt% of magnesium; The cobalt-based composite catalyst has an oxygen vacancy content of 20-60% and a specific surface area of ​​20-200 m 2 / g.

2. The cobalt-based composite catalyst according to claim 1, wherein The average particle diameter of the cobalt-based composite catalyst is 1-20 nm.

3. A method for preparing the cobalt-based composite catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-20 nm, and the specific surface area is 100-500 m 2 / g; (2) drying the mixture I to obtain the cobalt hydroxide nanosheets; the drying temperature is not higher than 40° C.; (3) crystallizing the cobalt hydroxide nanosheets and the cerium salt precursor in the presence of water to obtain a mixture II; the molar ratio of the cobalt element in the cobalt hydroxide nanosheets to the cerium element in the cerium salt precursor is 1:0.01-1 in terms of metal elements; (4) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based composite catalyst; The conditions of the second calcination treatment include: temperature of 200-800° C., heating rate of 2-20° C. / min, and time of 2-4 h.

4. The method according to claim 3, wherein: The method further comprises: first mixing magnesium oxide particles with water to obtain the magnesium hydroxide nanosheets; the conditions of the first mixing include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 10 min to 24 h.

5. The method according to claim 4, wherein: The magnesium oxide particles are obtained by subjecting a magnesium precursor to a first calcination treatment; the average particle diameter of the magnesium oxide particles is 5-30 nm.

6. The method according to claim 5, wherein: The conditions of the first calcination treatment include: temperature of 600-1000° C., heating rate of 2-20° C. / min, time of 2-4 hours, and air flow rate of 10-100 mL / min.

7. The method according to claim 5 or 6, wherein: The magnesium precursor is selected from at least one of light magnesium oxide, basic magnesium carbonate, and magnesium chloride hexahydrate.

8. The method according to any one of claims 3 to 7, wherein: In step (1), the amount of the cobalt salt precursor is such that the initial concentration of the cobalt element in the reaction system formed by the second mixture is 0.1-2 mol / L; and / or, In step (1), the cobalt salt precursor is selected from at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt sulfate heptahydrate, and cobalt acetate tetrahydrate.

9. The method according to any one of claims 3 to 8, wherein: In step (1), the second mixing conditions include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 2-30 h.

10. The method according to any one of claims 3 to 9, wherein: In step (2), the drying process is carried out at a temperature of 20-40°C and for a time of 20-26 hours.

11. The method according to any one of claims 3 to 10, wherein: In step (3), the amount of the cerium salt precursor used is such that the initial concentration of cerium in the reaction system formed by the crystallization treatment is 0.01-2.5 mol / L; and / or, In step (3), the cerium salt precursor is selected from at least one of cerous nitrate hexahydrate, cerous chloride heptahydrate, and cerous sulfate tetrahydrate.

12. The method according to any one of claims 3 to 11, wherein: In step (3), the conditions of the crystallization treatment include: temperature of 100-120° C. and time of 4-12 hours.

13. The method according to any one of claims 3 to 12, wherein: In step (4), the conditions of the second calcination treatment include: temperature of 200-400°C, heating rate of 3-15°C / min, time of 2-3h, and air flow rate of 10-100mL / min.

14. A cobalt-based composite catalyst prepared by the method according to any one of claims 3 to 13.

15. Use of the cobalt-based composite catalyst according to any one of claims 1 to 2 and 14 in the treatment of propane-containing gas; Preferably, the concentration of propane in the propane-containing gas is ≤5v%.

Citation Information

Patent Citations

  • Preparation method of cobalt-cerium composite oxide catalyst and cobalt-cerium composite oxide catalyst

    CN105214675A

  • High-activity and high-stability catalyst for catalytic oxidation of CO and preparation method of high-activity and high stability catalyst

    CN107876097A

  • Preparation method of cobalt oxide rich in oxygen vacancy for electrocatalytic water desorption and oxygen desorption

    CN113106486A

  • Cobalt-based perovskite oxide catalyst and preparation and application thereof

    CN116459840A

  • Preparation of alkali metal or alkaline earth metal promoted Co-based catalysts for the water gas shift reaction

    KR1020180092831A